Comparing the effect of different turbulence models on the CFD predictions of NACA0018 airfoil aerodynamics - Khan, Sher Afghan; Bashir, Musavir; Baig, Maugal Ahmed Ali; Mehaboob Ali, Fharukh Ahmed Ghasi (Penerbit Akademia Baru, 2020)
The analysis of aerodynamic forces on two-dimensional airfoils and flow phenomena associated with different Reynolds number has been widely investigated for aerospace vehicles and wind turbines. Various numerical methods have been used with different turbulence models, and the discrepancy in flow physics differs between each model. This work presents the numerical analysis of the aerodynamic performance of NACA 0018 airfoil using different turbulence models. The Computational Fluid Dynamics (CFD) solver, Ansys Fluent, is used for this numerical study. The available experimental data of NACA 0018 airfoil is used for comparing numerical outputs, and the difference in the lift, drag, and pressure coefficients are evaluated, respectively. Structured meshing is employed for all the investigated models for the analysis for lift and drag coefficients using four different turbulence models. Measurements of aerodynamic coefficients and surface pressures are recorded for a range of Re=0.8x105 to Re=0.3x106 and angles of attack (0° to 18°). The SST k-omega model provided the best lift coefficient predictions for low angles of attack Results also indicate that the flow separation regions and reattachment locations can be predicted by the Transition k-kl-ω model.